PENGARUH ENTRAINMENT DENGAN GELOMBANG SUARA 2000-2040 HZ DAN 2000-2090 HZ SECARA BINAURAL TERHADAP TAMPILAN BELAJAR, EKSPRESI GFAP POSITIF PADA ASTROSIT DAN PROSESUSNYA DI CA1 HIPPOCAMPUS TIKUS PUTIH (Rattus norvegicus) - , Zainuri Sabta Nugraha ([Yogyakarta] : Universitas Gadjah Mada, 2012)
It is known that the entrainment of high beta and gamma waves (20-40 Hz) in hippocampus can enhance its learning performance by improving the communication and strengthening of synapses. Astrocytic process associated with synapses in the CA1 hippocampus can modulate synaptic function and change the Long Term potentiation (LTP). This study aims to reveal the influence of binaural entrainment with sound waves of 2000-2040 Hz and 2000-2090 Hz on the expression of immunoreactive GFAP in the astrocyte in the rats, CA1 hippocampus, and its processes during operant learning condition. The subject of this research is a Wistar rat (rattus norvegicus), weighing 100- 150 grams and 4-6 weeks old. The subjects are divided into 5 groups (n=5). Groups P1a and P2 were given entrainment with 40 Hz sound wave while P3 was given entrainment with 90 Hz sound wave and the control (K) group that was not given any entrainment. Groups P2 and P3 were given learning test with Skinnerâs box every day for 12 days. One other groups was P1b that was only given learning test with Skinnerâs test every day for 12 days. This study showed no difference in the acquisition of reward (positive reinforcement) (p = 0.884), punishment (p = 0.141) and the learning performance (p = 0.449) between groups P1b, P2 and P3 were analyzed with One Way ANOVA and Kruskal-Wallis. Based on the evaluation of the immunohistochemistry, it is found that the lowest average amount of positive GFAP in astrocytes for the control group was 47.33 Â± 1.33 and the highest rate for P1 was 70.96 Â± 4.8. The lowest value of positive GFAP in astrocytes processes for control group was 30.87 Â± 2.69, while the highest value for P1 was 60.66 Â± 2.07. Histoscore index of positive GFAP astrocytes, the highest value for P2 was 115.58 Â± 14.13 and the lowest index in the control group was 16.05 Â± 1.64. The results of the experiment are analyzed with One Way ANOVA and Kruskal Wallis, and this research found that there are significant differences GFAP expression of astrocytes (p<0.004), astrocytes processes (p<0.006), and astrocytes histoscoer index (p<0.001). Moreover, this study found that there were no relationship between expression of GFAP in astrocytes and the processes of P2 and P3 groups of mice, and the operant learning conditions (p> 0.05) were tested using Pearson Product Moment correlation test. Overall, the results indicate that administration of entrainment by sound waves 2000-2040 and 2000-2090 Hz can increase GFAP expression in astrocytes and processes but did not affect the appearance of operant learning conditions.